(3dWdGH GdeLJeY hGdYdhe GdEOGQjIs - (3eMehO eMeO Sdje(B, (3UGdMs ((3YeGf(B:s (3ecJHI GdeLJeY GdYQHj ddfTQ h GdJhRjY(B,s, 2008)
(3YQhV hhUa GdHjGfGJ GdGMUGFjI, ebGjjS GdfRYI GdeQcRjI, ebGjjS GdJTJJ, GdeLehYGJ hWQb GdYbO, eHGOF fXQjI GdGMJeGdGJ, GdeJZjQGJ GdYThGFjI hGdJhRjYGJ GdGMJeGdjI, GdGQJHGW hGdGfMOGQ, GdCQbGe GdbjGSjI, GdSdGSd GdRefjIs
(3HHdjhZQGajG(B: (3U(B.321s
Keywords: (3GdGMJeGdGJs; (3GdGMUGAs